BLACK WOMEN IN HEAD POSITIONS - do Perpétuo Socorro Lima de Sousa, Maria (Revista Gênero e Interdisciplinaridade, 2024)
To check the way used by black women step into the professional space and assume the leadership positions, what kind of problems, devaluation and discrimination these women face. No difference by gender or race issue? Lay hold of popular knowledge that are seeking scientific slant as the research advances in this direction and do “deep diving” seeking confirmation of this knowledge is the spot we can ascertain from that “warrior-women” who faced this challenge and confirmed by the Institute of Economic Research (IPEA p. 3/2008). Regarding to the family, one of the main indicators to identify the changes and continuities in equality, especially between men and women - are us data over head of-family, grew up from 19.7% in 1993 to 28.8% in 2006. Nowadays there is much talk on diversity including gender, although this picture has not been painted, always like that, a short time ago the Brazilian colonial economy based on large rural properties and hand-slave labor gave little attention to formal education for men and none for women. The isolation, social stratification and patriarchal family relations favored a power structure based on unbounded authority of men landowners. Some changes only occurred after the arrival of the Portuguese Brazilian royal family, according Alves (2010): International migrations and economic diversification has increased the demand for education, which was seen as an instrument for social strata by intermediate. This brings the first impressions of the research that has as its background the woman ahead of sectors at a public institution at the time did not find projects to translate the expectations of professional mothers, wives, responsible for elderly parents or in moments of physical frailty and physiological, we expect to contribute to building political support that the woman is in a leading position and ahead of-other-fronts of-family or social work.